2009
DOI: 10.1007/s11255-009-9641-y
|View full text |Cite|
|
Sign up to set email alerts
|

Combination antioxidant effect of α-tocoferol and erdosteine in ischemia–reperfusion injury in rat model

Abstract: The erdosteine and α-tocoferol significantly reversed the effect of protein oxidation and lipid peroxidation induced by I/R shown by the decreased levels of MDA and XO activities. Both MDA and XO levels were found to be lower in group 6 compared to single agent treatment groups, and this was significantly different. All treatment groups showed increased SOD activity, which accounts for their oxidative properties. The mean Paller score of the combination treatment group (group 6) was lower than all groups excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
(33 reference statements)
1
14
0
3
Order By: Relevance
“…In the literature, there is no agreement on antioxidant enzyme levels in various organs during the I/R state. However, some studies that measured activities of SOD showed reduced levels of these enzymes (31,33,34). SOD protects cells against the toxic effects of superoxide radicals by catalyzing their conversion to H 2 O 2 (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is no agreement on antioxidant enzyme levels in various organs during the I/R state. However, some studies that measured activities of SOD showed reduced levels of these enzymes (31,33,34). SOD protects cells against the toxic effects of superoxide radicals by catalyzing their conversion to H 2 O 2 (30).…”
Section: Discussionmentioning
confidence: 99%
“…While the protective effect of vitamin E against AKI was first reported over 20 years ago, since then the therapeutic action of vitamin E has been demonstrated in many different animals (including mice [16,21], rats [13,22,23], rabbits [14], dogs [24], and pigs [25]) by using a variety of modeling methods (including ischemia/reperfusion [14,26,27], cisplatin [25,28], and other methods [13,29,30]), and has even been demonstrated in clinical studies [31,32] (Supplementary Table 1. Detailed information on the AKI models applied in the investigation of the protective effect of vitamin E).…”
Section: Therapeutic Action Of Vitamin E Against Akimentioning
confidence: 99%
“…In another study, Yurdakul et al reported that levels of MDA and xanthine oxidase were decreased by erdosteine treatment (19). To our knowledge, this is the first study demonstrating the protective effect of erdosteine on I/R injury by erythrocyte deformability in an experimental lower limb I/R injury rat model.…”
Section: Discussionmentioning
confidence: 60%